New English File. Pre-Intermediate: Student's Book - Oxenden C. Clive (Oxford, Oxford University Press, 2011)
Fun, motivating lessons that workThe perfect balance of grammar, vocabulary, pronunciation, and skills to help your students use English really effectively. A complete package for teachers and students The Teacher's Book gives you the support you need, and all the components work together for more effective learning.